A FIRST APPROACH TO THE STUDY OF THE CHILEAN CONSULAR REPRESENTATIONS IN THE NORTH PACIFIC TERRITORIES. THE CASE OF THE SANDWICH ISLANDS (1848-1852) (Tzintzun, Revista de Estudios Históricos, 2022)
The article reports the main milestones associated with the process of establishment and consolidation of the Chilean consular representations in the North Pacific territories, particularly in the Sandwich Islands —also known as the Kingdom of Hawaii— for the period between 1848 and 1852. Likewise, data is provided regarding the characters who headed such consulates, their suggestions to Santiago in the framework of the exercise of his position, the evolution of the position of the Chilean authorities towards the Kingdom of Hawaii and the Hawaiian trade situation.
Keywords: consul; Chile; Kingdom of Hawaii; trade